Incidence and morphological study of lice infested chicken (Gallus gallus domesticus) in Nineveh governorate, Iraq - Nadia H. mohammed; Rawaa G. Mohammed; Waad K. Khalaf (Iraqi Journal of Veterinary Sciences)
Lice were the most common Ectoparasites in birds, especially chickens that stay in their life cycle from eggs to the adult same bird, causing poor chicken health. The current study was conducted to detect lice infestation in 130 backyard chickens in some areas in Nineveh Governorate. The result indicated that the incidence of backyard chickens was 90(69.2%), and they were infested with two species of lice, Menacanthus stramineus and Lipeurus caponis. M. stramineus lice were the most prevalent, as they were observed on all parts of the chicken's body, recording a high infestation rate 61.5%, while the wing lice L. caponis recorded 30.8%. Lice infestation on one chicken varied between single and mixed infestation, with single infestation being the most common, reaching a rate of 80%, while mixed infestation reached 20%. Lice were identified by using a dissecting microscope and scanning electron microscopy to determine the exact structure of chewing lice, such as features of the head, chest, abdomen, legs, and claws of legs location and segmentation of antennae, setae of M. stramineus, and L. caponis. This study aimed to identify the morphological characteristics of lice isolated from backyard chickens using scanning and dissecting microscopes.